The Relationships Between Tendency to Aggression, Self-control, Mindfulness, and Happiness in Students of the Faculty of Health Sciences - Kaya, Esma Ulku (Png Publications, 2022)
Objectives: Previous studies focus on variables that reduce violence such as mindfulness, self-control, and happiness, but do not cover these relationships in a single study, creating a gap in the literature. The aim of this cross-sectional study was to investigate the relationships between aggression and these 3 variables in health science undergraduate students at a state university in Turkey. Methods: Students completed the aggression questionnaire, the Oxford happiness questionnaire short version, the brief self-control scale, and the mindful attention awareness scale. Results: In correlational analysis, only verbal aggression and happiness did not show a relationship. The result of hierarchical multiple regression analyses indicated that the most significant predictors that explained total aggression and aggression subscales were mindfulness and self-control, respectively. However, happiness did not have a significant link to either total aggression or subscales of aggression (except for hostility). Conclusions: The results emphasize that mindfulness and self-control may play important roles in reducing aggression. This study reveals the need for further analysis of the relationships between happiness and aggression and its subscales. Other implications are discussed.
Keywords: aggression; mindfulness; self-control; happiness; health sciences students